Risk without Reward? The Introduction of Bitcoin Spot ETFs - Pastorek, Daniel; Albrecht, Peter (Ekonomický časopis/Journal of Economics, 2026)
Our study examines to what extent the introduction of Bitcoin spot exchange-traded funds (ETFs) affected Bitcoin’s properties, including market dynamics, volatility, returns, return distribution, and tracking errors. Using block bootstrap simulations, OLS regression, EGARCH modeling, and non-parametric tests, we find that Bitcoin ETFs increase volatility and downside risk while leaving average returns unchanged. Return distribution shifts, including reduced skewness and kurtosis, suggest partial normalization, typically linked to greater liquidity and market participation. However, unlike traditional ETFs, Bitcoin ETFs introduce fail-to-deliver (FTD) occurrences, previously absent in Bitcoin markets, which mitigate extreme price movements through delayed settlement. Tracking error analysis confirms that spot ETFs more accurately track Bitcoin’s price than futures-based ETFs. These findings offer critical insights into Bitcoin ETFs’ market effects, particularly regarding stability and investor behavior.